2014
DOI: 10.1155/2014/237243
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Analysis of Software Change Propagation

Abstract: The object-oriented software systems frequently evolve to meet new change requirements. Understanding the characteristics of changes aids testers and system designers to improve the quality of softwares. Identifying important modules becomes a key issue in the process of evolution. In this context, a novel network-based approach is proposed to comprehensively investigate change distributions and the correlation between centrality measures and the scope of change propagation. First, software dependency networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Engineer CPI is calculated based on the number of incoming and outgoing workflows of the engineer in Engineer DSM, and PD is the geodesic shortest path from a component to another in Component DSM if there is a change propagated between those components in Change DSM (Pasqual and Weck 2011). Wang et al utilized network centrality metrics and their derivatives, which reflect the importance of nodes in the network in spreading information to identify their correlation with the scope of change propagation in a software class structure network (Wang et al 2014). Colombo et al investigated the architectural network features such as the number of components, modules, components in modules, bus elements, etc., on change propagation behavior of complex technical systems (Colombo et al 2015).…”
Section: Network Approachesmentioning
confidence: 99%
“…Engineer CPI is calculated based on the number of incoming and outgoing workflows of the engineer in Engineer DSM, and PD is the geodesic shortest path from a component to another in Component DSM if there is a change propagated between those components in Change DSM (Pasqual and Weck 2011). Wang et al utilized network centrality metrics and their derivatives, which reflect the importance of nodes in the network in spreading information to identify their correlation with the scope of change propagation in a software class structure network (Wang et al 2014). Colombo et al investigated the architectural network features such as the number of components, modules, components in modules, bus elements, etc., on change propagation behavior of complex technical systems (Colombo et al 2015).…”
Section: Network Approachesmentioning
confidence: 99%
“…Loch and Terwiesch [12] suggested that the reliability of upstream activities should be measured by the number of errors that occurred in the specific period of upstream activities. Some other scholars used the DSM matrix to study the dependence between elements in the system [16][17][18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e research aiming at solving such problems mainly focuses on the degree of dependence between activities; that is, the impact of changes in one activity on another activity. Information sensitivity modeling [2,[11][12][13][14][15] and DSM matrix [16][17][18] are the two key methods for this category. However, most of them neglected that the activity maturity is various according to time [13,15,19], which is an important prerequisite for subsequent analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In [59], the author developed a new centrality metric called CIRank (that keeps track of the changes propagating among classes in a software dependency network) and observed it to be significantly correlated with the degree and PageRank centrality metrics on the basis of the Spearman's rank-based correlation coefficient. In [60], the Kendall's concordance-based correlation measure was used to assess the correlation between eight different centrality metrics that are suitable for gene regulatory networks in E. Coli.…”
Section: Related Work and Our Contributionsmentioning
confidence: 99%